Combinatorial mutagenesis and fermentation optimization biotechnologies synergistically enhance monacolin K content in functional red yeast rice - Wu, Zhengyan; Zhang, Chan; Liu, Qing; Zhang, Song; Yang, Qi; Liu, Jun; Lu, Dong; Zhou, Xiang (Frontiers in Microbiology, 2025)
IntroductionRed yeast rice (RYR) is produced through solid-state fermentation by Monascus genus. Its functional component, Monacolin K (MK), has the same structure as lovastatin and can effectively inhibit HMG-CoA reductase, thereby reducing serum cholesterol.MethodsA combinatorial mutagenesis strategy integrating atmospheric room-temperature plasma and heavy-ion radiation was employed to generate mutant strains. The optimizations of substrate components and conditions were carried out during solid-state fermentation (SSF). Subsequently, RYR enriched with MK was produced through scale-up experiments. Additionally, integrated biosynthetic pathway with expression dynamics of MK biosynthetic gene cluster to reveal the efficient biosynthesis of MK in a mutant strain.ResultsA mutant M. purpureus CSUFT-1, which exhibited a remarkable 1.67-fold increase in MK production during SSF compared to the original strain, was obtained. Through refinement of SSF parameters, specifically, adding optimized corn steep liquor adjuvant solution [60% (v/v) corn steep liquor, pH modulation at 5, 3 g/L of MgSO4·7H2O, 1.5 g/L of KH2PO4] with 20% (v/w) of injection volume, the MK yield was significantly amplified to 32.71 mg/g on day 28. Scale-up experiments confirmed the robustness of the optimized process, with MK production stabilizing approximately at 24.66 mg/g. RT-qPCR results showed that seven key genes, including mokC (6.8-fold upregulation) and mokF (22-fold upregulation), were significantly activated during the early stage of fermentation to drive precursor synthesis, only mokE gene exhibited the sustained overexpression in M. purpureus CSUFT-1 during the entire SSF.DiscussionThis work successfully demonstrates a synergistic approach combining advanced combinatorial mutagenesis with precise bioprocess optimization to substantially improve MK yield. The overproducing M. purpureus CSUFT-1 and the optimized SSF protocol provide both microbial resource and technical protocol for industrial-scale production of RYR with high MK.